2018
DOI: 10.1007/s00395-018-0682-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: NR4A1 aggravates the cardiac microvascular ischemia reperfusion injury through suppressing FUNDC1-mediated mitophagy and promoting Mff-required mitochondrial fission by CK2α

Abstract: Mitochondrial fission and mitophagy are considered key processes involved in the pathogenesis of cardiac microvascular ischemia reperfusion (IR) injury although the upstream regulatory mechanism for fission and mitophagy still remains unclear. Herein, we reported that NR4A1 was significantly upregulated following cardiac microvascular IR injury, and its level was positively correlated with microvascular collapse, endothelial cellular apoptosis and mitochondrial damage. However, NR4A1-knockout mice exhibited re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
216
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(232 citation statements)
references
References 64 publications
9
216
2
Order By: Relevance
“…These conclusions identify mitochondrial fragmentation as the upstream mediator and trigger event for mitochondrial damage. Our finding is similar to previous studies showing that mitochondrial fragmentation is the pathogenesis for fatty liver [59], gastric cancer [60], cardiac ischaemia-reperfusion injury [15] and diabetic cardiomyopathy [12]. Finally, we found that mitochondrial fragmentation could be repressed by MKP1 via inhibiting the JNK-CaMKII-Fis1 pathway.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These conclusions identify mitochondrial fragmentation as the upstream mediator and trigger event for mitochondrial damage. Our finding is similar to previous studies showing that mitochondrial fragmentation is the pathogenesis for fatty liver [59], gastric cancer [60], cardiac ischaemia-reperfusion injury [15] and diabetic cardiomyopathy [12]. Finally, we found that mitochondrial fragmentation could be repressed by MKP1 via inhibiting the JNK-CaMKII-Fis1 pathway.…”
Section: Discussionsupporting
confidence: 81%
“…Moderate mitochondrial division helps mitochondria to remove the damaged parts and ensure the homeostasis of the mitochondrial network [13]. However, uncontrolled mitochondrial division, as evidenced by extensively fragmented mitochondria, represses the ability of mitochondria to produce sufficient ATP and finally contribute to the opening of the mitochondrial apoptotic pathway [14,15]. Although mitochondrial fragmentation is observed in hyperglycaemia-challenged cardiomyocytes [12], the role of mitochondrial fragmentation is not defined in diabetic renal damage.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mitophagy is the result of fusion between mitochondria and lysosome. The green mitochondria locate with red lysosome would generate the orange mitophagy [43]. Then, the number of orange dot was measured to quantify the number of mitophagy.…”
Section: Immunofluorescence Confocal Microscopymentioning
confidence: 99%
“…Normal mitochondria produce ATP to fuel cellular metabolism through oxidative phosphorylation [9]. However, damaged mitochondria liberate the proapoptotic factors, such as cyt-c, into the cytoplasm, thereby initiating caspase-9-related programmed cell death [10]. Numerous studies have identified mitochondria as potential targets to regulate the progression of renal IR injury [11-16].…”
Section: Introductionmentioning
confidence: 99%